Effect of Competition and Incentive on Employee Performance - Anizir Ali Murad; Ladika Ladika; Mustika Mustika; Pandu Adi Cakranegara; Imam Jayanto (Budapest International Research and Critics University, 2022)
This research tries to analyze about effect of competition and incentive on employee performance. The object of research at PT. Pundi Masberjaya. The population in this study were employees of PT. Pundi Masberjaya, totaling 51 people. The sampling method of this study used saturated sampling. So, the sample in this study was 51 people. The method of data analysis in this study used multiple linear regression using partial test (t). The results show that competition and incentive have positive and significant effect on employee performance at PT. Pundi Masberjaya.